LEGALITY AND CONTROVERSY: THE DEATH PENALTY IN INDONESIA FROM THE PERSPECTIVES OF ISLAMIC LAW, CRIMINAL LAW AND HUMAN RIGHTS - Mohas, Muhyi; Rofiana, Reine; Jastisia, Mentari; Anwar, Jarkasi; Risyawan, Alief (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
The legality of the death penalty remains controversial as it often conflicts with the right to life. Therefore, this study was aimed to examine the legality of imposing death penalty from the perspectives of Criminal Law, Islamic Law, and Human Rights. This research used normative legal research and empirical research methods. The result showed that The death penalty in Aceh is known as